Dystocia Due to Hydramnios and Uterine Inertia in aJaffarabadi Buffalo - parmar, kirankumar; Raval, Rupesh; Vala, Karsan; Devmurari, Yash; Dhruv, Vadher; Pranami, Ruchir; Patel , Meet (The Indian Journal of Animal Reproduction, 2024)
The present clinical case reports the successful delivery of a fetus by induced calving in the hydramnios condition inJaffarabadi buffalo. The buffalo was presented with 320 days of gestation. The parturition was induced with prostaglandinand steroids. The dead fetus with jaw defect was relieved by traction. The dam had an uneventful recovery.
Keywords: Dystocia; Hydramnion; Uterine inertia; affarabadi buffalo